Interférences artistiques dans l'æuvre de Roger Martin du Gard - Emeis, Harald (Wydawnictwo Naukowe UAM, 2003)
The article deals with the ways in which Roger Martin du Gard, makes use of elements drawn from other fields of artistic activity such as sculpture, painting, music, dance, and cinema, in his writings. The object of this paper is an analysis of the novelist's purpose and of the effect that the technique in question has on the reader.
The intermingling of artistic elements in the writings of Roger Martin du Gard
Keywords: Gard du, Roger Martin